ANALISIS DAYA SAING DAN FAKTOR PENENTU EKSPOR KOMODITAS UNGGULAN INDONESIA KE ORGANISASI KERJASAMA ISLAM (OKI) - Deki Sunardi; Rina Oktaviani; Tanti Novianti (JURNAL EKONOMI DAN KEBIJAKAN PEMBANGUNAN, 2014)
Organization of Islamic Cooperation or OIC is an association of Islamic countries in the world which is made up of 57 countries, including Indonesia. OIC has great potential as a destination for the export market. The purpose of this study is to analyze the competitiveness of Indonesian exports to OIC and determinants that influence it. Competitiveness of commodities analyzed using the RCA, IIT and EPD, while the determinants of export using the gravity model analysis. The results showed that 86,7 percent from fifteen commodities that have the largest export value had RCA more than one and seven commodity have market position as rising star, but from IIT analysis showed that integration of economics still not strong enough. Factors that influence a positive and significant impact on Indonesia's commodity exports to OIC are per capita income, real exchange rate and a common language, while the negative effects are the gdp per capita difference, economic distance and tarrif. Key words: RCA, IIT, EPD, Gravity Model